Strategic differences in trampoline gymnastics between Japanese and world athletes - Shintani, S.; Yamazaki, H.; Sugita, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2022)
Trampoline gymnastics have been included in the Olympic Games since the 2000 Sydney Olympics. Since then, many more countries have started programs for development of trampoline gymnastics. Although trampoline gymnastics include individual, synchronized and team events, only individual performance is included in the Olympics. Trampoline gymnastics include an initial routine and a second routine. The present study focused only on the second routine, and was designed to clarify how addition of the T score in 2011 has affected current trampoline gymnastics. The results of the World championships and All Japan championships held between 2011 and 2019 were compared, and the total scores and other scores were investigated. The transition evident in scores from 2011 to 2019 suggested that Japanese male athletes have lagged behind the world`s top players, whereas Japanese women athletes have been rapidly closing in on the top flight. Examination of the relationship between the total score and other scores for the top 30 male athletes in the 2019 World championships showed a strong positive correlation with the E score (r = 0.70). For women, on the other hand, there was a strong positive correlation with the T score (r = 0.71). These results may provide a useful basis for devising a strategy aimed at improvement of performance.